Analisis Risiko Kesehatan Akibat Paparan Bahan Kimia Berbahaya Pada Lingkungan Kerja Industri: Literature Review - Cynthia Winanda; Anisah Fitri Rahmasari Harahap; Nadia Aulia Putri Nasution; Abdurrozzaq Hasibuan (Annusfy : Journal of Multidisciplinary Research, 2026)
Exposure to hazardous chemicals in industrial work environments remains a critical issue due to its potential to cause various health risks among workers. This study aims to analyze health risks resulting from exposure to hazardous chemicals in industrial workplaces. The method used was a descriptive literature review of 10 scientific articles published between 2021–2025 from Google Scholar, SINTA, and Portal Garuda databases. The results indicate that exposure to chemicals such as benzene, ammonia, hydrogen sulfide (H₂S), and BTX (Benzene, Toluene, Xylene) presents low to moderate risk levels but still impacts health, particularly with long-term exposure. The identified effects include respiratory disorders, nervous system disturbances, and reproductive health issues. It is concluded that even below threshold limit values, exposure still poses risks, thus comprehensive control measures are needed through OHS implementation, proper use of PPE, and improved supervision